ASSOCIATIVE MEANING IN HOHO LYRICS OF NIAS TRADITIONAL SONG - Devy Kristiana Wau; Willem Saragih (State University of Medan, 2017)
This study deals with the use of Associative meaning in Hoho lyrics of Nias traditional songs which consisted of 4 songs, they are hoho wangowai dome, hoho famadaya hasijimate, hoho moyo, and hoho faluaya. The objectives of this study were to to find out the types of associative meaning and to describe the types of associative meaning of hoho lyrics. This research used descriptive qualitative research.There were five types of associative meaning applied in hoho lyrics namely, connotative meaning, stylistic meaning, affective meaning, reflected meaning and collocative meaning. The data were taken from the words, phrases or sentences from hoho lyrics. The finding implied that the number of associative meaning was described as follows: connotative meaning 50%, stylistic meaning 16,74%, affective meaning 23,47%, reflected meaning7,05%,and collocative meaning 2,95%. Out of 170 hoho expressions there were 85 expressions which belong to connotative meaning. It indicated that the most dominantly type used was connotative meaning with percentage of 50% due to the song contained with prayer, victory, happiness, honour, wishes or hopes